2002
DOI: 10.1128/jvi.76.19.9588-9599.2002
|View full text |Cite
|
Sign up to set email alerts
|

Replication of a Cytopathic Strain of Bovine Viral Diarrhea Virus Activates PERK and Induces Endoplasmic Reticulum Stress-Mediated Apoptosis of MDBK Cells

Abstract: Endoplasmic reticulum (ER) stress signaling is an adaptive cellular response to the loss of ER Ca 2؉homeostasis and/or the accumulation of misfolded, unassembled, or aggregated proteins in the ER lumen. ER stress-activated signaling pathways regulate protein synthesis initiation and can also trigger apoptosis through the ER-associated caspase 12. Viruses that utilize the host cell ER as an integral part of their life cycle would be predicted to cause some level of ER stress. Bovine viral diarrhea virus (BVDV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
138
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(146 citation statements)
references
References 57 publications
(86 reference statements)
6
138
1
Order By: Relevance
“…Although the NS3/ NS3∆50 protein induces caspase-8-and -9-dependent apoptosis, several lines of evidence suggest that several factors (cellular and/or viral) or activation pathways of apoptosis are likely to be involved in the BVDV-associated apoptosis process. The facts that oxidative stress is observed in cells infected with cp BVDV [40], and that caspase-12-associated ER stress, a feature that was not addressed in this study, is observed in cp BVDV-induced apoptosis are consistent with the latter statement [18]. Caspase-12, which resides within the cytoplasmic side of the ER, is believed to play a central role in the ER stress-mediated apoptosis [31] and can activate caspase-8 [7] which in turn stimulates, through Bid processing, cytochrome c release and activates caspase-9 [17].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Although the NS3/ NS3∆50 protein induces caspase-8-and -9-dependent apoptosis, several lines of evidence suggest that several factors (cellular and/or viral) or activation pathways of apoptosis are likely to be involved in the BVDV-associated apoptosis process. The facts that oxidative stress is observed in cells infected with cp BVDV [40], and that caspase-12-associated ER stress, a feature that was not addressed in this study, is observed in cp BVDV-induced apoptosis are consistent with the latter statement [18]. Caspase-12, which resides within the cytoplasmic side of the ER, is believed to play a central role in the ER stress-mediated apoptosis [31] and can activate caspase-8 [7] which in turn stimulates, through Bid processing, cytochrome c release and activates caspase-9 [17].…”
Section: Discussionsupporting
confidence: 85%
“…In addition, oxydative stress [40], intracellular viral RNA accumulation [44], caspase-12-associated ER stress [18], and mitochondriadependent caspase-9 activation [11] have been reported to be associated with cp BVDV-induced apoptosis. Here we show that NS3/NS3∆50 of BVDV induced apoptosis, and correlated with both caspase-8 and caspase-9 activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known that UPR can activate proapoptotic gene expression (such as that of GADD153), which in turn can induce infected cells to undergo apoptosis (23,33,61). Expression levels of GADD153 were increased only in rSV5V⌬C-infected cells (consistent with the induction of apoptosis seen in rSV5V⌬C-infected cells).…”
Section: Discussionmentioning
confidence: 57%
“…Similarly to proteasomal inhibition, unchecked viral replication in malignant cells leads to an accumulation of viral proteins. Several reports have highlighted the importance of ER stress in the response to viral infection (Jordan et al, 2002;Su et al, 2002). The ER is essential for the folding and posttranslational modification of viral proteins.…”
Section: Discussionmentioning
confidence: 99%